Genetically predicted asthma and the risk of abnormal spermatozoa - Li, Zhichao; Teng, Zhihai; Han, Zhenwei; Zhang, Yanping; Wang, Yaxuan (Frontiers in Genetics, 2024)
Background: Several previous animal and human studies have found a strong association between asthma and spermatozoa quality, but whether these associations are causal or due to bias remains to be elucidated.Methods: We performed a two-sample Mendelian randomization (MR) analysis to assess the causal effect of genetically predicted asthma on the risk of abnormal spermatozoa. Asthma, childhood-onset asthma (COA), and adult-onset asthma (AOA) (sample sizes ranging from 327,670 to 408,442) were included as the exposures. Genetic information for abnormal spermatozoa was obtained from a genome-wide association study (GWAS) comprising 209,921 participants. In univariable MR (UVMR) analysis, the inverse variance weighted (IVW) method was conducted as the primary method, with the MR Egger and weighted median used as supplementary methods for causal inference. Sensitivity analyses, including the Cochran Q test, Egger intercept test, MR-PRESSO, and leave-one-out analysis, were performed to verify the robustness of the MR results. Multivariable MR (MVMR) was conducted to evaluate the direct causal effects of asthma on abnormal spermatozoa risk.Results: UVMR detected causal associations between genetically predicted asthma and an increased risk of abnormal spermatozoa (OR: 1.270, 95% CI: 1.045-1.545, p=0.017). Moreover, we found that AOA (OR:1.46, 95% CI: 1.051,2.018, p=0.024) has positive causal effects on the risk of abnormal spermatozoa rather than COA(p=0.558). Sensitivity analysis found little evidence of bias in the current study(p>0.05). MVMR further confirmed that asthma directly affected the risk of abnormal spermatozoa.Conclusions: Our MR study suggested that genetically predicted asthma could be associated with an increased risk of abnormal spermatozoa, and similar results were obtained in AOA. Further studies are warranted to explain the underlying mechanisms of this association and may provide new avenues for prevention and treatment.